Kinetic processes in the high-temperature pressure-infiltration of Al into Al2O3. (1st May 2020) - Schneider, Gionata; Fornabaio, Marta; Weber, Ludger; Mortensen, Andreas
Graphical abstract: Abstract: We explore the influence (i) of the interaction between aluminium and alumina, and (ii) of sodium impurities present in Bayer alumina, on the pressure infiltration of alumina particle preforms with molten aluminium. At 1000°C or above, although the aluminium/alumina system is non-reactive, capillarity-driven solution-reprecipitation processes cause the liquid-solid interface to become mobile. Data show that this can result in infiltration kinetics that resemble those observed with reaction-driven pressure infiltration, namely a continuously increasing melt saturation under fixed infiltration pressure. Resulting isobaric saturation velocities are measured at 1000°C, 1050°C and 1100°C. The role of alumina particle shape and of Na-containing inclusions is investigated. It is found that the main factors affecting the rate of high-temperature isobaric infiltration in this system is the particle geometry. Measured steady infiltration rates give an activation volume on the order of ≈ 200 nm 3 and an activation energy in the range of 300-500 k J m o l, suggesting that isobaric infiltration kinetics are governed by diffusion through the solid alumina. Sodium impurities of Bayer alumina are present within β ″-Al2 O3 . They do not influence steady pressure infiltration but ease initial melt penetration into the preform, possibly because evaporated Na2 O alters the oxide skin layer that lines the surface of molten aluminium.